Empty Sella Syndrome as a Window Into the Neuroprotective Effects of Prolactin - Paul, David A.; Strawderman, Emma; Rodriguez, Alejandra; Hoang, Ricky; Schneider, Colleen L.; Haber, Sam; Chernoff, Benjamin L.; Shafiq, Ismat; Williams, Zoë R.; Vates, G. Edward; Mahon, Bradford Z. (Frontiers in Medicine, 2021)
BACKGROUND. The goal of this study was to relate diffusion MR measures of white matter integrity of the retinofugal visual pathway with prolactin levels in a patient with downward herniation of the optic chiasm secondary to medical treatment of a prolactinoma. METHODS. A 36-year-old woman with a prolactinoma presented with progressive bilateral visual field defects nine years after initial diagnosis and medical treatment. She was diagnosed with empty-sella syndrome and instructed to stop cabergoline. Hormone testing was conducted in tandem with routine clinical evaluations over one year and the patient was followed with diffusion magnetic resonance imaging (dMRI), optical coherence tomography (OCT), and automated perimetry at three time points. Five healthy controls underwent a complementary battery of clinical and neuroimaging tests at a single time point. RESULTS. Shortly after discontinuing cabergoline, diffusion metrics in the optic tracts were within the range of values observed in healthy controls. However, following a brief period where the patient resumed cabergoline (of her own volition), there was a decrease in serum prolactin with a corresponding decrease in visual ability and increase in radial diffusivity (p<0.001). Those measures again returned to their baseline ranges after discontinuing cabergoline a second time. CONCLUSIONS. These results demonstrate the sensitivity of dMRI to detect rapid and functionally significant microstructural changes in white matter tracts secondary to alterations in serum prolactin levels. The inverse relations between prolactin and measures of white matter integrity and visual function are consistent with the hypothesis that prolactin can play a neuroprotective role in the injured nervous system.